'You can dance your prototype if you like': independent filmmakers adapting the hackathon. Issue 3 (3rd July 2017) - Karlsen, Joakim; Løvlie, Anders Sundnes
ABSTRACT: Hackathon-style events are increasingly used to facilitate cross-disciplinary learning and innovation in the media industries. Based on an observational study of a hackathon organized as part of the film festival Nordic Panorama (NP) we analyse the challenges in using the hackathon format to facilitate cross-disciplinary learning and innovation for filmmakers, developers and designers. We find that many participants experienced frustrations resulting from a lack of programming skills and their expectation that the hackathon should result in 'something digital'. Additionally, ideals for authorship embedded in the working cultures of film and TV professionals impeded the team's ability to involve all participants on an equal footing. As implications for future hackathons we suggest organizers should consider using tools for end-user development and generative toolkits to facilitate digital making and collaborative learning. We also suggest similar events should avoid including project owners if the group work is based on existing projects.